Transmembrane channel activity in human hepatocytes and cholangiocytes derived from induced pluripotent stem cells. Issue 7 (15th March 2022) - Florentino, Rodrigo M.; Li, Qin; Coard, Michael C.; Haep, Nils; Motomura, Takashi; Diaz‐Aragon, Ricardo; Faccioli, Lanuza A. P.; Amirneni, Sriram; Kocas‐Kilicarslan, Zehra N.; Ostrowska, Alina; Squires, James E.; Feranchak, Andrew P.; et al.
Abstract: The initial creation of human‐induced pluripotent stem cells (iPSCs) set the foundation for the future of regenerative medicine. Human iPSCs can be differentiated into a variety of cell types in order to study normal and pathological molecular mechanisms. Currently, there are well‐defined protocols for the differentiation, characterization, and establishment of functionality in human iPSC‐derived hepatocytes (iHep) and iPSC‐derived cholangiocytes (iCho). Electrophysiological study on chloride ion efflux channel activity in iHep and iCho cells has not been previously reported. We generated iHep and iCho cells and characterized them based on hepatocyte‐specific and cholangiocyte‐specific markers. The relevant transmembrane channels were selected: cystic fibrosis transmembrane conductance regulator, leucine rich repeat‐containing 8 subunit A, and transmembrane member 16 subunit A. To measure the activity in these channels, we used whole‐cell patch‐clamp techniques with a standard intracellular and extracellular solution. Our iHep and iCho cells demonstrated definitive activity in the selected transmembrane channels, and this approach may become an important tool for investigating human liver biology of cholestatic diseases. Abstract : Transmembrane Channel Activity in Human Hepatocytes and Cholangiocytes Derived from Induced Pluripotent Stem Cells.image